Silver Nanoparticles: Green Synthesis, Characterization, and Their Usage in Determination of Mercury Contamination in Seafoods. (4th February 2014) - Ahmed, Muhammad Ahad; Hasan, Najmul; Mohiuddin, Shaikh
Abstract : We demonstrate that silver nanoparticles undergo an interaction with Hg 2+ found in traces. The PEG-PVP-stabilized Ag nanoparticles were successfully synthesized via a reduction approach and characterized with surface plasmon resonance UV/Vis spectroscopy. By utilizing the redox reaction between Ag nanoparticles and Hg 2+, and the resulted decrease in UV/Vis signal, we develop a colorimetric method for detection of Hg 2+ ion. A linear and inversely proportional relationship was found between the absorbance intensity of the Ag nanoparticles and the concentration of Hg 2+ ion over the range from 10 ppm to 1 ppm at absorption on 411 nm. The detection limit for Hg 2+ ions in homogeneous aqueous solutions is estimated to be 1 ppm. This system shows excellent selectivity for Hg 2+ . The results found have potential implications in the development of new colorimetric sensors for easy and selective detection and monitoring of mercuric ions in aqueous solutions. The proposed method was successfully applied to quantify the amount of mercury in seafood.